First spatial and high-resolution imaging in perfused pig heart: intracellular 3D monitoring of myoglobin, cytochromes, and subcellular structures of myocytes by use of EMPHO-Oxyscan - Rauh, Robert; Böhnert, Markus; Mahlke, Christine; Kessler, Manfred (Proceedings Volume 4241, Saratov Fall Meeting 2000: Optical Technologies in Biophysics and Medicine II, 2001)
Living tissue of mammals contains a large amount of subcellular particles like mitochondria that are involved in light scattering. Since these particles correlate in a certain way with the functional status of cells, light scattering may be useful for monitoring of functional tissue state. With EMPHO SSK Oxyscan we investigated functional parameters in a new kind of isolated perfused pig heart model. In this perfusion model we use organs obtained from the abattoir that are reperfused by use of a heart-lung machine. By creating 3D images of tissue light scattering we found an interesting relation between morphological structures of myocardium and the patterns of the 3D images. Additionally, we created 3D images of myoglobin oxygenation. Furthermore, we got spectra showing the redox state of cytochromes. We believe that this new kind of tissue imaging method will give us the opportunity to get new insights into myocardial functio